2005
DOI: 10.1177/008124630503500401
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders in South African Males: A Review of the Clinical Presentation of Hospitalised Patients

Abstract: South African literature on males with eating disorders is scarce. The existence of these disorders in South Africa males requires documentation; hence the current study was under taken. Specifically, the research attempted to identify features that were present in males in a South African hospital setting which specialises in the treatment of eating disorders. This research was then compared to contemporary international literature. The patient sample (n = 17) constituted all males who were admitted into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moreover, associated clinical issues were somewhat different to the international literature. Specifically it was found that mood and obsessive-compulsive disorders were infrequent but relational difficulties were common in the study by Freeman and Szabo (2005), notably father -son issues. This study thus provided some unique insights, involving a South African patient population.…”
Section: Gender -The Existence Of Male Sufferersmentioning
confidence: 81%
See 2 more Smart Citations
“…Moreover, associated clinical issues were somewhat different to the international literature. Specifically it was found that mood and obsessive-compulsive disorders were infrequent but relational difficulties were common in the study by Freeman and Szabo (2005), notably father -son issues. This study thus provided some unique insights, involving a South African patient population.…”
Section: Gender -The Existence Of Male Sufferersmentioning
confidence: 81%
“…Within the South African context there was no such data. A paper by Freeman and Szabo (2005) comprised a review of clinical data of 17 male eating disordered patients admitted for treatment over a period of 10 years (1993 -2002). The majority were diagnosed with anorexia nervosa (76%).…”
Section: Gender -The Existence Of Male Sufferersmentioning
confidence: 99%
See 1 more Smart Citation